2007
DOI: 10.1073/pnas.0609879104
|View full text |Cite
|
Sign up to set email alerts
|

Rab27b regulates number and secretion of platelet dense granules

Abstract: The Rab27 GTPase subfamily consists of two closely related homologs, Rab27a and Rab27b. Rab27a has been shown previously to regulate organelle movement and regulated exocytosis in a wide variety of secretory cells. However, the role of the more restrictedly expressed Rab27b remains unclear. Here we describe the creation of Rab27b knockout (KO) strain that was subsequently crossed with the naturally occurring Rab27a KO line, ashen, to produce double KO (Rab27a ash/ash Rab27b ؊/؊ ) mice. Rab27b KO (and double KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
165
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(173 citation statements)
references
References 37 publications
(49 reference statements)
5
165
2
1
Order By: Relevance
“…Furthermore, the migration induced by 0.5 or 0.1 mM ATPγS was dramatically inhibited in Rab27a-deficient microglia ( Figure 7C and 7D), consistent with the important role of Rab27a in the trafficking and exocytosis of lysosomes [9,10]. The result that the microglial migration induced by 1 mM ATPγS was not significantly affected in Rab27a-deficient mice ( Figure 7B) suggest that other subtypes of Rab GTPase, for example Rab27b [28,35,36], may partially compensate for the lysosome deficiency in these mice. Rab27a has been suggested to be associated specifically with secretory lysosomes or lysosome-related organelles in some cells derived from the hematopoietic lineage [9,10], from which microglia are also considered to be derived.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, the migration induced by 0.5 or 0.1 mM ATPγS was dramatically inhibited in Rab27a-deficient microglia ( Figure 7C and 7D), consistent with the important role of Rab27a in the trafficking and exocytosis of lysosomes [9,10]. The result that the microglial migration induced by 1 mM ATPγS was not significantly affected in Rab27a-deficient mice ( Figure 7B) suggest that other subtypes of Rab GTPase, for example Rab27b [28,35,36], may partially compensate for the lysosome deficiency in these mice. Rab27a has been suggested to be associated specifically with secretory lysosomes or lysosome-related organelles in some cells derived from the hematopoietic lineage [9,10], from which microglia are also considered to be derived.…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, we found no such effects with Rab27A in vitro and in vivo [3]. Common, but also different nonredundant functions of Rab27A versus Rab27B have been described dependent on the cell type and/or secretory process studied [11][12][13][14]. Interestingly, Wang et al (2008) reported Rab27A-dependent invasion and xenograft metastasis of ER-negative, already invasive, MDA-MB-231 and MDA-MB-435 breast cancer cells.…”
Section: Rab27b-mediated Vesicle Transport Regulates Breast Cancer Cecontrasting
confidence: 46%
“…(51) However, analysis of mice lacking Rab27a and/or Rab27b function has shown that Rab27a and Rab27b appear to have an additive effect on 5-hydroxytriptamine release from platelet dense granules. (52) Also, recent analysis of Rab27a and Rab27b null mice has shown that Rab27a and Rab27b regulate NADPH oxidase release in neutrophils through independent mechanisms. (33) In stimulation-dependent RANKL release in osteoblastic cells, the function of Rab27a and Rab27b does not seem to be redundant because individual knockdown of each of these genes resulted in a significant reduction in RANKL release to the cell surface (Fig.…”
Section: Discussionmentioning
confidence: 99%